Pengetahuan tentang Sukuk Tidak Mempengaruhi Masyarakat untuk Berinvestasi Sukuk - Fayakhun Bakhtiar (JESI (Jurnal Ekonomi Syariah Indonesia), 2019)
This study aims to find the relationship between the knowledge of society about islamic bonds (sukuk) with the interest of public investment to islamic bonds (sukuk). The research method used is descriptive correlation with cross sectional time approach done in Sleman regency. Sampling technique in this study using non probability sampling with consecutive sampling method. The number of samples is 90 respondents with data collection using questionnaires. Data were analyzed using chi-square. The result of research shows that there is no relationship between the knowledge of islamic bonds (sukuk) and the public interest to invest in islamic bonds (sukuk). Knowledge only has an effect of 14.3%.